Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s40268-017-0222-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Fixed-Dose Co-Formulation of Daclatasvir, Asunaprevir, and Beclabuvir on the Pharmacokinetics of a Cocktail of Cytochrome P450 and Drug Transporter Substrates in Healthy Subjects

Abstract: BackgroundA fixed-dose combination of daclatasvir (DCV; hepatitis C virus NS5A inhibitor), asunaprevir (ASV; non-structural protein 3 inhibitor), and beclabuvir (BCV; non-structural protein 5B inhibitor) is approved in Japan for hepatitis C virus genotype 1.ObjectiveThe objective of this study was to assess the combination’s drug–drug interaction potential in vivo using a validated cocktail of eight cytochrome P450 (CYP) and transporter probes.MethodsWe conducted an open-label single-sequence study in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Nowadays, different antiviral strategies such as, capping the virus particle which enables tethering within 549-776 amino acid residues (GO:0003968) and this stretch of amino acids is crucial for RNA synthesis (Figure 3). Beclabuvir is a non-nucleoside polymerase inhibitor that potentially inhibit nonstructural protein 5B (NS5B) of HCV (Garimella, Tao et al 2018). Upon intracellular uptake beclabuvir allosterically binds to the noncatalytic Thumb 1 site (Figure 4) of viral RdRp which slowdown the RNA synthesis process (Garimella, Tao et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, different antiviral strategies such as, capping the virus particle which enables tethering within 549-776 amino acid residues (GO:0003968) and this stretch of amino acids is crucial for RNA synthesis (Figure 3). Beclabuvir is a non-nucleoside polymerase inhibitor that potentially inhibit nonstructural protein 5B (NS5B) of HCV (Garimella, Tao et al 2018). Upon intracellular uptake beclabuvir allosterically binds to the noncatalytic Thumb 1 site (Figure 4) of viral RdRp which slowdown the RNA synthesis process (Garimella, Tao et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Beclabuvir is a non-nucleoside polymerase inhibitor that potentially inhibit nonstructural protein 5B (NS5B) of HCV (Garimella, Tao et al 2018). Upon intracellular uptake beclabuvir allosterically binds to the noncatalytic Thumb 1 site (Figure 4) of viral RdRp which slowdown the RNA synthesis process (Garimella, Tao et al 2018). However, in the case of SARS-CoV-2 beclabuvir occupies the active site environment (ASE), ( Figure 5) of the RdRp which is essential for the RNA-dependent polymerase activity (Fouad, Soliman et al 2019) ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study suggest that ATP binding domain and RNA-directed 5'-3' polymerase activity of the RdRp exist within 549 th to 776 th amino acid residues (GO:0003968) and this stretch of amino acids is crucial for RNA synthesis (Figure 3). Beclabuvir is a non-nucleoside polymerase inhibitor that potentially inhibit nonstructural protein 5B (NS5B) of HCV [25]. Previous studies, including phase 3 clinical trials have suggested beclabuvir have a high response rate at post-treatment week [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the pharmacokinetic, efficiency and tolerability were also reported very favorable [28]. Upon intracellular uptake beclabuvir allosterically binds to the non-catalytic Thumb 1 site (Figure 4) of viral RdRp which slowdown the RNA synthesis process [25]. However, in the case of RdRpSARS-CoV-2 beclabuvir occupies the active site environment (ASE), ( Figure 5) is essential for the RNA-dependent polymerase activity [18,19] ).…”
Section: Discussionmentioning
confidence: 99%
“…The drug interaction between metoprolol and daclatasvir/asunaprevir/beclabuvir has been studied in vivo [ 20 ] (Table 3 ); however, this regimen is not licensed in Europe and the USA. Garimella and colleagues [ 20 ] showed that asunaprevir affected the metoprolol plasma concentration as it is a moderate inhibitor of CYP2D6. In vitro experiments have shown that daclatasvir is not an inhibitor of CYP2D6 [ 20 – 22 ].…”
Section: Drug Interactions Between Cardiovascular Drugs (Cvds) and DImentioning
confidence: 99%